2015
DOI: 10.1007/s10147-015-0829-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose chemotherapy with methotrexate and vinblastine for patients with desmoid tumors: relationship to CTNNB1 mutation status

Abstract: MTX and VBL treatment every other week is well tolerated and achieved a favorable response in patients resistant to meloxicam treatment, regardless of CTNNB1 mutation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
(48 reference statements)
0
21
3
1
Order By: Relevance
“…However, this evidence was not confirmed by other groups who reported a statistically not significant trend of poorer outcome in patients harboring the S45F mutation or no correlation between the specific CTNNB1 mutation and RFS (Mullen et al, 2013;Romero et al, 2012). Regarding the impact of mutations on response to medical treatment, Nishida et al did not find a correlation between the efficacy of methotrexate or vinblastine and specific CTNNB1 mutations (Nishida et al, 2015). On the other hand, only the S45F mutation was significantly associated with a poor response to meloxicam (Hamada et al, 2016) and with a progression arrest rate after imatinib treatment (Kasper et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, this evidence was not confirmed by other groups who reported a statistically not significant trend of poorer outcome in patients harboring the S45F mutation or no correlation between the specific CTNNB1 mutation and RFS (Mullen et al, 2013;Romero et al, 2012). Regarding the impact of mutations on response to medical treatment, Nishida et al did not find a correlation between the efficacy of methotrexate or vinblastine and specific CTNNB1 mutations (Nishida et al, 2015). On the other hand, only the S45F mutation was significantly associated with a poor response to meloxicam (Hamada et al, 2016) and with a progression arrest rate after imatinib treatment (Kasper et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Regarding the impact of mutations on response to medical treatment, Nishida et al . did not find a correlation between the efficacy of methotrexate or vinblastine and specific CTNNB1 mutations (Nishida et al ., ). On the other hand, only the S45F mutation was significantly associated with a poor response to meloxicam (Hamada et al ., ) and with a progression arrest rate after imatinib treatment (Kasper et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Considering these enigmatic behaviors, the therapeutic approach for extra-peritoneal DF has been shifting from surgery with a wide surgical margin to conservative therapy [7, 8]. Recently, several therapeutic modalities for DF were reported including ‘wait & see’ only [9], COX-2 inhibitor therapy [10], hormonal therapy [11], low-dose chemotherapy [12], and tyrosine kinase inhibitors [13, 14], while few studies have investigated the prognosticators of these conservative therapies thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that desmoid tumors with different CTNNB1 mutations have diverse tumorigenic potency against various treatment modalities. Desmoid tumors with S45F mutation had higher rates of local recurrence after surgery [10,12,13], and greater resistance to meloxicam treatment [14], whereas the efficacy of low-dose chemotherapy was not associated with the mutation status of CTNNB1 [15]. Taking these findings into consideration, the mutation status of CTNNB1 in desmoid tumors would appear to alter not only tumorigenicity, but also the responsiveness to surgical and conservative treatment.…”
Section: Introductionmentioning
confidence: 99%